The Combination of Dysexecutive and Amnestic Deficits Strongly Predicts Conversion to Dementia in Young Mild Cognitive Impairment Patients: A Report from the Gothenburg-Oslo MCI Study - Hessen, Erik (S. Karger AG, 2014)
BACKGROUND/AIMS: The present study aimed to add to the knowledge of mild cognitive impairment (MCI) by studying the prognosis in a relatively young cohort of patients characterized by neuropsychological criteria. METHODS: Patients (mean age: 63 years) with cognitive complaints and MCI (n = 302) were recruited from two university clinics and followed for 2 years. RESULTS: Pure dysexecutive MCI occurred in 11.7% of the neuropsychologically impaired patients, while 59.3 and 29.0% were characterized as having pure amnestic MCI or multidomain MCI. During the study period, the state of 2 (10.5%) of the patients with single-domain dysexecutive MCI converted to dementia, while 28 (29.2%) of the patients with pure amnestic MCI became demented. Of the patients with both executive and amnestic deficits, 28 (59.6%) became demented. CONCLUSION: The results suggest that dysexecutive symptoms in combination with amnestic symptoms constitute a strong risk factor for dementia in young MCI patients. A significant number of patients in all subgroups showed normal test results at follow-up, indicating that a neuropsychological diagnosis needs to be supported by imaging or biomarker data.